Spirulina extract improves age-induced vascular dysfunction. (31st December 2022) - Majewski, Michal; Klett-Mingo, Mercedes; Verdasco-Martín, Carlos M.; Otero, Cristina; Ferrer, Mercedes
Abstract: Context: Vascular dysfunction is considered a hallmark of ageing that has been associated with altered vasomotor responses, in which nitric oxide (NO) and reactive oxygen species participate. The consumption of Spirulina extracts, with antioxidant properties, increased recently. Objective: This study investigates the effect of Spirulina aqueous extract (SAE) on the vascular function of the aorta from aged rats. Materials and methods: Aortic segments from aged male Sprague-Dawley rats (20–22 months old) were exposed to SAE (0.1% w/v, for 3 h) to analyse: (i) the vasodilator response induced by acetylcholine (ACh), by the NO donor sodium nitroprusside (SNP), by the carbon monoxide releasing molecule (CORM) and by the KATP channel opener, cromakalim (CK); (ii) the vasoconstrictor response induced by KCl and noradrenaline (NA); (iii) the production of NO and superoxide anion, and (iv) the expression of the p-eNOS and HO-1 proteins. Results: Incubation with SAE increased the expression of p-eNOS (1.6-fold) and HO-1 (2.0-fold), enhanced NO release (1.4-fold in basal and 1.9-fold in ACh-stimulated conditions) while decreased the production of superoxide (0.7-fold). SAE also increased the sensitivity (measured as pEC50 ) to ACh (control: −7.06 ± 0.11; SAE: −8.16 ± 0.21), SNP (control: −7.96 ± 0.16; SAE: −9.11 ± 0.14) and CK (control: −7.05 ± 0.39; SAE: −8.29 ± 0.53), and potentiated the response to KCl (1.3-fold) and to NA (1.7-fold). Conclusion: The antioxidant properties of SAE improved the vasomotor responses of aorta from aged rats. These results may support the use of Spirulina as a protection against vascular dysfunction.